Effects of respiratory muscle work on exercise performance - Harms, C. A.; Wetter, T. J.; St. Croix, C. M.; Pegelow, D. F.; Dempsey, J. A. (Journal of Applied Physiology, 2000)
The normal respiratory muscle effort at maximal exercise requires a significant fraction of cardiac output and causes leg blood flow to fall. We questioned whether the high levels of respiratory muscle work experienced in heavy exercise would affect performance. Seven male cyclists [maximal O2 consumption (O2) 63 ± 5 ml · kg1 · min1] each completed 11 randomized trials on a cycle ergometer at a workload requiring 90% maximal O2. Respiratory muscle work was either decreased (unloading), increased (loading), or unchanged (control). Time to exhaustion was increased with unloading in 76% of the trials by an average of 1.3 ± 0.4 min or 14 ± 5% and decreased with loading in 83% of the trials by an average of 1.0 ± 0.6 min or 15 ± 3% compared with control (P < 0.05). Respiratory muscle unloading during exercise reduced O2, caused hyperventilation, and reduced the rate of change in perceptions of respiratory and limb discomfort throughout the duration of exercise. These findings demonstrate that the work of breathing normally incurred during sustained, heavy-intensity exercise (90% O2) has a significant influence on exercise performance. We speculate that this effect of the normal respiratory muscle load on performance in trained male cyclists is due to the associated reduction in leg blood flow, which enhances both the onset of leg fatigue and the intensity with which both leg and respiratory muscle efforts are perceived.